2005
DOI: 10.1097/01.olq.0000175384.44106.be
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of HIV and Sexually Transmitted Infections Among Indirect Sex Workers in Cambodia

Abstract: These data suggest high sexual risk among beer girls in Cambodia. Targeted and frequent HIV and STI interventions are urgently needed in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 17 publications
3
30
2
1
Order By: Relevance
“…HIV infection rate for FSW was quite high in our study and is comparable to the rate found in Cambodia (Kim et al 2005). In other previous FSW studies, HIV seroprevalence rates were as high as 75% in Kisumu (Kenya), 69% in Ndola (Zambia), 55% in Cotonou (Benin) and 34% in Yaounde, Cameroon (Morison et al 2001) and as low as Sample size for some variables may be lower due to missing records; * Reference age category for university students was <25; ** Region of origin and were categorised as regions based on cultural similarities, grand north (Adamawa, North, Far north provinces), Other (Centre, East, Littoral, Northwest, West, South and Southwest).…”
Section: Discussionsupporting
confidence: 90%
“…HIV infection rate for FSW was quite high in our study and is comparable to the rate found in Cambodia (Kim et al 2005). In other previous FSW studies, HIV seroprevalence rates were as high as 75% in Kisumu (Kenya), 69% in Ndola (Zambia), 55% in Cotonou (Benin) and 34% in Yaounde, Cameroon (Morison et al 2001) and as low as Sample size for some variables may be lower due to missing records; * Reference age category for university students was <25; ** Region of origin and were categorised as regions based on cultural similarities, grand north (Adamawa, North, Far north provinces), Other (Centre, East, Littoral, Northwest, West, South and Southwest).…”
Section: Discussionsupporting
confidence: 90%
“…Indirect FSW were distinguished from direct FSW, generally working in entertainment establishments as beer promotion girls, waitresses, hostesses or karaoke girls, for example, and engaged in occasional transactional sex for supplementary income. [21][22][23] In 1997, an estimated 5300 women worked in the entertainment/ service sector and 6000 were brothel-based FSW. The number of women involved in entertainment-based sex work has grown dramatically in recent years in Cambodia.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…National screening and prevention programs for C. trachomatis infection have been implemented, usually among young adults, in industrialized countries (11,14,16). With the exception of sporadic testing of commercial sex workers, Chlamydia screening is rare in developing countries, which have the highest incidence of new chlamydial infections (7,9,17,25). The major barriers to screening programs in the developing world include the high cost of testing and the lack of appropriate staff and diagnostic tools.…”
mentioning
confidence: 99%